Adenoviruses - Desheva, Yulia (IntechOpen, 2019)
Adenoviruses are among the most studied and at the same time most mysterious of viruses. In this book, the authors highlight the achievements in the study of animal and human adenoviruses, chemotherapy of adenovirus infections, and the development in adenoviral vector-based vaccines and gene therapy. I believe that this book will be useful not only for researchers but also in solving specific medical problems.